Kekudusan Hidup Seperti Yesus sebagai Bentuk Profesionalisme Guru PAK - Agustihana Delvryance; Marse Marse; Herlis Djawa Rama Awang; Seldjatem, Cristian (Publisher STPKat, 2024)
The professionalism of CHG (PAK) teachers is a crucial element in improving the quality of education and shaping student character. The example expected of a PAK CHG teacher is holiness of life like Jesus Christ. This article outlines the relationship between the professionalism of PAK teachers and holiness of life as an example, as taught in the Bible. The research method used is qualitative, by collecting information from various sources of literature that can be accounted for academically. The results show that holiness of life according to the Bible refers to separation from sin and evil, and being like Jesus Christ who is holy. The professionalism of PAK teachers includes personality competence, where being a role model is a key aspect. PAK teachers are required to live in holiness and imitate the life of Jesus. Holiness of life becomes the foundation for the professionalism of PAK teachers, which is then implemented in providing examples to students. This study concludes that to achieve holiness of life, self-knowledge and self-control are needed, as well as awareness of the importance of obeying biblical teachings in daily life. Thus, being holy like Jesus is a true form of professionalism for PAK teachers